Characterization of Cellulose Derived from Invasive Alien Species Plant Waste for Application in the Papermaking Industry: Physic-Mechanical, Optical, and Chemical Property Analysis - Antía Iglesias; Ángeles Cancela; Ana Soler Baena; Ángel Sánchez (Applied Sciences, 2023)
This study examines the potential of four invasive plant species, both arboreal and herbaceous, within the riparian forest of the Umia River in Galicia, a common ecosystem in northern Spain. These invasive species (Arundo donax, Phytolacca americana, Eucalyptus globulus, and Tradescantia fluminensis) were collected and assessed for their suitability as an alternative source of pulp and paper materials for the paper industry to mitigate the environmental impacts associated with conventional cellulose fiber production from harmful monocultures. Cellulosic material from leaves, bark, and/or stems of each of the selected species was isolated from lignin and hemicelluloses through kraft pulping processes. Resulted fibers and pulps were analyzed visually, morphologically, chemically, and mechanically to evaluate their papermaking properties. To compare these properties with those of commercially available pulp, test sheets were concurrently produced using commercial bleached Eucalyptus cellulose. The findings reveal that the employed fibers exhibit promising characteristics for artistic paper production. Regarding the pulp, two refining times were tested in a PFI machine, and the Schopper–Riegler degree was measured. Paper sheets underwent various tests to determine thickness, basis weight, apparent volume, apparent density, permeability, and chemical composition, as well as microscopic optical and morphological properties. The fibers obtained from the waste derived from the removal of invasive exotic species and biodiversity control present a viable and intriguing alternative for decentralized paper production, yielding noteworthy results for the creative sector. This research highlights the potential of harnessing invasive species for sustainable and innovative paper manufacturing practices.